Smart integrated sensors in real time monitoring critical parameters in tissue culture growth room of oil palm - Aziz N.H.A.; Wahab N.A.; Muhamad W.N.W.; Alias A.J.; Hashim A.T.; Mustafa R. (IEEE Computer Society, 2023)
Real-time monitoring critical parameters can be enhanced by extending the alert system via email and short messaging system (SMS) technology. The aim of the smart integrated sensors is to remotely monitor critical parameter in tissue culture growth room. The tissue culture laboratory provides the oil palm industry with innovations for the production of improved planting materials and information on the molecular biology of tissue culture processes. Research has shown that factors such as temperature, humidity, liquid, phase and gas compositions are critical in producing quality clonal materials using tissue culture process. Therefore, it is necessary to provide good physical and chemical conditions for production of quality products. Consequently, sensors are required to monitor and record the data in growth room. SHT11 sensors are used to monitor parameters of temperature and humidity along with an optical sensor system for liquid phase and composition monitoring. In support to monitor gaseous in the vessels, sensors of oxygen, carbon dioxide and ethylene are utilized in the tissue culture growth room. Thus, a smart integrated sensors system is developed to monitor all influenced parameters in the culture growth room linked to the database and analysis software. 2009 IEEE.